Cefazolin plasma concentrations in children less than 25 kilograms undergoing elective cardiac surgery: an audit of current clinical practice at Red Cross War Memorial Children's Hospital - Dresner, Alexandra (Department of Anaesthesia, 2014)
Includes bibliographical references.